Characteristics of patients with gestational loss and abortion attended at the Instituto Nacional Materno Perinatal (2022): A descriptive study - Silva Dominguez, Daniel (2024)
Objective. To determine the characteristics of antibiotic prescriptions in pregnant women attended at the National Maternal Perinatal Institute (INMP) from July 2019 to June 2021. Materials and Methods. This is a quantitative, descriptive,retrospective, cross-sectional study. A data collection form was applied to gather variables related to antibiotic prescriptions, and the data were entered into a Microsoft Excel database for analysis using SPSS software. Results. The studyevaluated antibiotic prescriptions in 328 pregnant women, accounting for 10.87% of the total population. The majority (65%) were prescribed a single antibiotic. Urinary tract infections (37.80%) and preoperative antibiotic prophylaxis(54.27%) were the main reasons for prescriptions. Beta-lactams were the most prescribed group (84.14%), followed bylincosamides (14.93%). Most prescriptions were made in the third trimester (82.1%), with Cefazolin 1g and Cephalexin500 mg being the most prescribed. Lower prescription rates were observed in the second and first trimesters, with Ceftriaxone 2g and Cefuroxime being the most used, respectively. The majority of the prescribed antibiotics fell into FDAcategory B (93.3%), with a minority in category D (6.7%). Conclusion. 10.87% of the pregnant women attended at theINMP were prescribed antibiotics, with urinary tract infections and preoperative antibiotic prophylaxis being the mostcommon indications. The beta-lactam group of antibiotics was the most prescribed, significantly predominating over othergroups like lincosamides